2011
DOI: 10.1002/app.34667
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticle deposition on hydrophilic multilayer film surface and its effect on antimicrobial activity

Abstract: Silver nanoparticles were deposited on the surface of the external polyamide 6 (PA6) layer of a multilayer film, by spraying and ultrasound-assisted methods. The effect of silver nanoparticles content and deposition method on the mechanical and optical properties of the multilayered films as well as the efficiency of silver ion release and their fungicidal characteristics were evaluated. Itaconic (IA) and Maleic anhydride (MA) were used as adhesion promoter agents for preventing the agglomeration of the silver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Untreated PP showed no antibacterial activity. This result is in good agreement with Ag/polyimide nanocomposite with Ag loading of 0.06 wt % 8. The antibacterial mechanism observed in the composites is possibly due to Ag + biocide released from polymer nanocomposites 8, 11…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Untreated PP showed no antibacterial activity. This result is in good agreement with Ag/polyimide nanocomposite with Ag loading of 0.06 wt % 8. The antibacterial mechanism observed in the composites is possibly due to Ag + biocide released from polymer nanocomposites 8, 11…”
Section: Resultssupporting
confidence: 85%
“…These results are in good agreement with previous studies of Ag incorporation into polymer nanocomposites. 8,11,26 Using a calibration method,8, 11, 26 the quantitative amount of Ag + release can be determined. The concentration of Ag + released from the SiO 2 @Ag NPs/polypropylene composite is in good agreement with that released from the Ag/PP composite 26.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several kinds of antimicrobial molecules from different families have been used, such as acids, amino acids, alcohols, terpenes, peptides, proteins, polysaccharides antiseptics, metal oxides, and metal salts . Many additives have been tested to obtain the best antimicrobial activity and to create an optimal material.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11] Several kinds of antimicrobial molecules from different families have been used, such as acids, [12][13][14][15][16] amino acids, 11,17 alcohols, terpenes, [18][19][20] peptides, proteins, [21][22][23][24] polysaccharides 25,26 antiseptics, [27][28][29][30][31][32][33] metal oxides, and [34][35][36] metal salts. [37][38][39][40][41][42] Many additives have been tested to obtain the best antimicrobial activity and to create an optimal material. A previous study has demonstrated the antimicrobial activity of acrylate hydrogels in which silver acetate was introduced.…”
Section: Introductionmentioning
confidence: 99%